PENGARUH BAURAN PEMASARAN TERHADAP LOYALITAS KONSUMEN BUAH MELON GOLDEN (Cucumis Melo L) di PT. MEKAR UNGGUL SARI, BOGOR, JAWA BARAT - Rangga Aldion; Ali Ibrahim Hasyim; Ktut Murniati (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2020)
The purpose of this study was to analyze the marketing mix, the level of consumer loyalty to the consumption of melon fruit and the effects of the marketing mix on the loyalty of melon consumers at PT. Mekar UnggulSari, Bogor, West Java. Data were collected in September until November 2018. The research was conducted at PT. Mekar Unggul Sari, Bogor, West Java as a case study. Respondents in the study amounted to 89 people with the sampling technique used was no-probability sampling with accidental sampling. The results of the study explain that the marketing mix elements used as variables in this study are the elements of the product, price, place and promotion. The level of consumer loyalty of melon fruit at PT. Mekar Unggul Sari in this study is at the liking the brand level. The average score on the variable consumer loyalty obtained is 4.38 or it can be said that the level of loyalty of melon consumers score is 93.26% at the level of liking the brand.Key words: effect, loyalty of consumer, marketing mix